Response of rice yield, grain quality to chilling at grain filling stages - Guo, Erjing; Wang, Lizhi; Shi, Yanying; Jiang, Shukun; Cheng, Xue; Chen, Xi; Ma, Haoyu; Wan, Nenhan; Bai, Fan; Zhang, Zhentao; Zhang, Tianyi; Li, Tao; et al. (Wiley, 2024)
This study aims to quantify the impacts of chilling at the grain filling stage on rice yield and grain quality. A factorial experiment with four levels of temperature and duration of chilling treatments at the early and late grain filling stages was conducted in 2017, 2018 and 2019.RESULTSPer 10 °C·day increase in the accumulated cooling degree day at the early and late grain filling stages, the rice emergence–maturity duration was delayed by 0.8% (0.6%) and rice yield decreased by 2.2% (1.7%). Chilling at the early grain filling stage decreased the rice heading rate, while chilling at the late grain filling stage increased rice amylose but decreased protein content. For chilling treatment at the early grain filling stage, rice yield and grain quality were mainly correlated with seed‐setting rate, whereas for chilling treatment at the late grain filling stage the rice yield and grain quality were mainly correlated with 1000‐grain weight.CONCLUSIONThis study improved the understanding of how chilling at the grain filling stages affects rice phenology, yield and grain quality, providing a theoretical basis for maintaining rice yield while ensuring grain quality. The results could be used to guide the rice‐growing community in combating chilling at grain filling stages. © 2024 Society of Chemical Industry.